Review Artikel: Aplikasi Ekstrak Daun Binahong (Anredera cordifolia) dalam Berbagai Sediaan Farmasi dan Kosmetik - Tusilva, Arina; Asysyifa Naila; Aulia Joza Putri; Aulia Wulan; Dea Wulandari; Dini Mariessa (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Anredera cordifolia (Ten.) Steenis, commonly known as binahong, is a traditional medicinal plant widely used in Indonesia due to its secondary metabolites such as flavonoids, saponins, tannins, alkaloids, and triterpenoids, which exhibit antibacterial, antioxidant, and wound-healing properties. These potentials have encouraged numerous studies on the development of pharmaceutical and cosmetic formulations derived from binahong leaf extract. This review aims to evaluate research findings related to various binahong-based formulations, including creams, patches, serums, lipid nanoparticle gels, antibacterial gels, and balms. The review of six studies revealed that cream and patch formulations were effective in accelerating wound healing, particularly in diabetic wounds. Red binahong leaf serum demonstrated very strong antioxidant activity with an IC50 value of less than 30 ppm, indicating its potential as an anti-aging agent. Lipid nanoparticle gel formulations showed optimal particle sizes (50–100 nm), although further optimization of pH and viscosity was still required. Antibacterial gel was proven to inhibit Staphylococcus epidermidis growth with an inhibition zone up to 9.13 mm. Meanwhile, binahong balm exhibited high practical value and user acceptability, with the 20% concentration being the most preferred. Overall, the findings highlight that binahong leaf extract is highly versatile in various pharmaceutical and cosmetic dosage forms, offering great potential to be developed into effective, safe, and community-accepted natural products.